Electrospun drug blended poly(lactic acid) (PLA) nanofibers and their antimicrobial activities - Duygulu, Nilufer Evcimen; Ciftci, Fatih; Ustundag, Cem Bulent (SPRINGER, 2020)
In the present study, the influence of electrospinning parameters on poly(lactic acid) (PLA) nanofiber production and antimicrobial attitude of drug blending were investigated. The PLA concentrations (5 to 12% wt/v) were determined with solvent ratio variations of a triple solvent system (chloroform (CHL), dimethylformamide (DMF) and tetrahydrofuran (THF)). Flow rates were varied from 0.5 to 1 mL/h, while voltages were changed from 10 to 15 kV, and 10 kV voltage and 0.5 mL/h flow rate were selected as optimum electrospinning conditions. According to morphological investigations via scanning electron microscopy, the average PLA fiber diameters varied from 303 to 405 nm, for 5 and 8% wt/v PLA concentrations, respectively. The drug (ceftriaxone disodium) was blended into these concentrations and electrospun. Drug addition reduced the fiber diameters, and at 8% wt/v drug blended PLA concentrations homogeneous fiber distribution was obtained. Additionally, the antimicrobial attitude of drug blended PLA nanofibers was analyzed by using agar disc diffusion method and antimicrobial activity against Escherichia coli, and Listeria monocytogenes were observed.
Keywords: Electrospinning parameters; Poly(lactic acid); Ceftriaxone disodium; Triple solvent system; POLYMER NANOFIBERS; RELEASE; FIBERS; DELIVERY; SCAFFOLDS; FABRICATION; Polymer Science